Heparan sulfate and syndecan-1 are essential in maintaining murine and human intestinal epithelial barrier function - Bode, Lars (American Society for Clinical Investigation, 2007)
Patients with protein-losing enteropathy (PLE) fail to maintain intestinal epithelial barrier function and develop an excessive and potentially fatal efflux of plasma proteins. PLE occurs in ostensibly unrelated diseases, but emerging commonalities in clinical observations recently led us to identify key players in PLE pathogenesis. These include elevated IFN-γ, TNF-α, venous hypertension, and the specific loss of heparan sulfate proteoglycans from the basolateral surface of intestinal epithelial cells during PLE episodes. Here we show that heparan sulfate and syndecan-1, the predominant intestinal epithelial heparan sulfate proteoglycan, are essential in maintaining intestinal epithelial barrier function. Heparan sulfate– or syndecan-1–deficient mice and mice with intestinal-specific loss of heparan sulfate had increased basal protein leakage and were far more susceptible to protein loss induced by combinations of IFN-γ, TNF-α, and increased venous pressure. Similarly, knockdown of syndecan-1 in human epithelial cells resulted in increased basal and cytokine-induced protein leakage. Clinical application of heparin has been known to alleviate PLE in some patients but its unknown mechanism and severe side effects due to its anticoagulant activity limit its usefulness. We demonstrate here that non-anticoagulant 2,3-de-O-sulfated heparin could prevent intestinal protein leakage in syndecan-deficient mice, suggesting that this may be a safe and effective therapy for PLE patients.